A comparison of preparing curved canals using NiTi Engine-driven and K-flexo endodontic instruments (Mustansiria Dental Journal, 2018)
The purpose of this in vitro study was to evaluate the combined effect of ProTaper file rotary instruments to K-flexo file hand instruments in curved canals in terms of instrumentation time, change in working length, and spreader penetration depth. Thirty curved mesial canals of extracted mandibular molars were used in this study, divided into two groups (15) canals for each group. In group I the canals were prepared with NiTi ProTaper file with slow speed contra angle hand piece (300rpm). In group II the canals were prepared by step-back technique with Gates-Glidden using stainless steel K-flexo hand instruments. Students't-test revealed that there was a highly significant difference between group I and group II in preparation time, and change in working length. In group II spreader penetrated significantly closer to working length than in group I.